Do remittances worsen export diversification? - Erik Vardanyan (Kiel Institute for the World Economy (IfW), 2019)
The paper explores the impact of workers' remittances on the level of export diversification. The hypothesis is that significant inflow of remittances causes overvaluation of real exchange rate, which in turn deteriorates diversity of export. The theoretical base is in line with the Dutch disease phenomenon. The paper uses annual cross-national panel data over 2000-2016 period and System GMM methodology. The evidence suggests that indeed large inflow of remittances is associated with less diversified export. The economic intuition behind is that remittance-caused real exchange rate appreciation unevenly suppresses export of goods: some goods "suffer" more than others do. In terms of the number of product-names, a percentage point increase in remittances to GDP sent home "reduces" variety of export by approximately five active lines. There are other interesting findings as well. An improvement of government effectiveness facilitates overall export diversification; terms of trade improvement and rise of real exchange rate volatility mostly increase export concentration rather than alter number of exported product-names.
Keywords: F14; F24; F31; 330; remittances; export diversification; export concentration; export variety; real exchange rate; System GMM